Inference-based form selection in native and non-native speakers: Evidence from subject-verb agreement error detection in French - Frimu, Rodica; Dekydtspotter, Laurent (Lingua, 2022)
•Selecting specified over underspecified forms requires real-time inferences.•Real-time inferences flesh out underspecified contents.•Inferences in computing sentence meaning and form selection compete for resources.•The competition for resources is in evidence when processing capacity is reduced.•Competition is salient in L2 learners and reduced capacity processing in natives. This study examines native and non-native retrieval of the third person number agreement morphology for the French future tense (e.g. mangera (eat-fut.3ps.sg) vs. mangeront (eat-fut.3ps.pl), ‘will eat’), in the light of subset and superset-based late-insertion models. We present evidence for the coactivation of subset vocabulary items where selecting the more specified item -ont (3ps.pl) in third-person plural agreement requires eliminating the less specified item –a (3ps.sg). The lack of plural specification for –a is interpreted as [-Plural] by a real-time inference on a < -ont, -a > information scale defined by [Number: Ø/Plural]. Using picture classification time differences during a grammaticality judgment task, we argue that i.) subset vocabulary items are activated and that ii.) domain-general inferencing enables form selection in multiple activations. Hence, picture-probes related to the ongoing interpretation of the sentence presented immediately after a mismatching singular verb form (subset item error) took longer to classify in L1-English L2-French learners and in French natives tested with a speeded task. This interaction of form with meaning construction justifies subset access triggering domain-general inference-based selection in multiple activations over a superset-based model of vocabulary item activation or information-load and frequency-based approaches. This model provides an understanding of temporary irretrievability in L2 acquisition.